The law regulating the work of associations and other institution working in the field of non-governmental organizations = قانون تنظيم عمل الجمعيات وغيرها من المؤسسات العاملة فى مجال العمل الاهلى - Egpyt (2025)
Law no. 10 of the year 2017 on issuing the law regulating the work of associations and other institutions working in the field of non-governmental work – part 1: definitions – part 2: associations – part 3: public benefit associations – part 4: non-governmental institutions – part 5: foreign non-governmental organization – part 6: national agency for the regulation of the work of the foreign non-governmental organizations – part 7: the non-governmental associations and institutions support funds – part 8: the general federation, the regional and specific federations – part 9: penalties قانون رقم 70 لسنة 2017 بإصدار قانون تنظيم عمل الجمعيات وغيرها من المؤسسات العاملة فى مجال العمل الاهلى – الباب الأول التعريفات – الباب الثانى الجمعيات – الباب الثالث الجمعيات ذات النفع العام – الباب الرابع المؤسسات الاهلية – الباب الخامس المنظمات الاجنبية غير الحكومية – الباب السادس الجهاز القومى لتنظيم عمل المنظمات الاجنبية غير الحكومية – الباب السابع صندوق دعم الجمعيات والمؤسسات الاهلية – الباب الثامن الاتحاد العام والاتحادات الاقليمية والنوعية – الباب التاسع العقوبات